Trends in long‐term outcomes of patients with HCV‐associated hepatocellular carcinoma after hepatectomy: A comparison before and after introduction of direct‐acting antivirus therapy - Fumiaki Munekage; Tomoaki Yoh; Satoshi Ogiso; Takuya Kato; Nguyen Hai Nam; Kazuyuki Nagai; Yoichiro Uchida; Takashi Ito; Takamichi Ishii; Etsuro Hatano (Annals of Gastroenterological Surgery, 2024)
Abstract Backgrounds The success of direct‐acting antiviral (DAA) therapy provides a cure for patients chronically infected with hepatitis C virus (HCV); however, outcomes after hepatectomy for HCV‐associated hepatocellular carcinoma (HCC) before and after DAA introduction remain poorly studied. Methods Patients who underwent R0/R1 hepatectomy for HCV‐associated HCC were retrospectively analyzed. Two time periods were defined: Pre‐DAA (2007–2011, December 2013 was defined as the end of follow‐up) and Post‐DAA groups (2014–2018, December 2020 was defined as the end of follow‐up). Propensity score matching (PSM) analyses were performed to highlight the effect of DAA therapy. Results A total of 155 patients with HCV‐associated HCC were included in this study (Pre‐DAA group, n = 103 and post‐DAA group, n = 52). In the Post‐DAA group, DAA therapy was performed in 26 patients (50.0%), and all of these patients achieved sustained virologic response (SVR) (preoperative SVR, n = 7; postoperative SVR, n = 19). There was no significant difference between the two groups regarding surgical settings and tumor pathology. There was no significant difference in the 5‐year overall survival (OS) rate (61.1% and 64.8%, pre‐ and post‐DAA group, respectively, p = 0.441); meanwhile, the 5‐year recurrence‐free survival (RFS) rate in the post‐DAA group was better than the pre‐DAA group (21.1% and 40.2%, p = 0.073) with a trend toward significance. After PSM except for the postoperative SVR status, there were no significant differences in OS (p = 0.586) and RFS (p = 0.888). Conclusions This study showed that survival outcomes were not changed in hepatectomized cases of HCV‐associated HCC before and after the introduction of DAA therapy.